Midnight at the Electric - Anderson, Jodi Lynn (HarperTeen, an imprint of HarperCollins Publishers, 2017)
In the months before her one-way trip to Mars, Adri Ortiz is sent to Wichita to live with a elderly cousin and finds herself fixating on where she came from and the stories of two women who lived more than a hundred years earlier.